Opportunities for Development of Cactus (Opuntia spp.) in Arid and Semi-arid Regions - Felker, Peter; Singh, Gurubachan; Pareek, O P (Annals of Arid Zone, 2016)
Cactus, a CAM plant, grows extensively in arid and semi-arid parts of the world. It possesses a very high water to dry matter conversion efficiency and has immense economic value as fruit, vegetable, fodder, medicine, etc. The importance of cactus pear as livestock feed has been discussed in detail, giving techniques for utilization as’ forage. Since the quality of the cactus c1adodes does not deteriorate on storage and as they maintain green color as well as vitamin A level, they can provide an excellent source of fodder during the drought periods. The red/orange fruits of the cacti are edible, range in weight from 110 to 160 g and contain 12 to 15% sugar. The cladodes of the nopalito cacti are used as vegetable. Some of these types are known to reduce blood sugar level in the human body. Cactus pear is also a source of red cochineal dye and mucilage for binders and thickening agents. The status of recently introduced cactus pear clones in Indian arid and semi-arid regions has been discussed.